Impact of COVID-19 Related Knowledge and Precautions on Emotional and Behavioral Problems Among Children During the Post-pandemic in China: The Explanatory Value of Emotional Problems Among Caregivers - Wang, Jingyi; Chen, Yun; Guo, Xiaoqin; Lin, Haijiang; Richards, Marcus; Wang, Hao; Chen, Xiaoxiao; Fu, Chaowei (Frontiers in Psychology, 2021)
To investigate the prevalence of emotional and behavioral problems (EBPs) among children during the COVID-19 post-pandemic in China; examine associations between COVID-19 related knowledge and precautions and children’s problems, and explore the potential explanatory value of caregivers’ mental health status on any associations observed. Based on a cross-sectional design, caregivers of 6017 students from twelve primary schools in Shanghai and Taizhou, China, were invited to complete an online survey from June 26 to July 6, 2020. Children’s EBPs were assessed using the Strengths & Difficulties Questionnaire (SDQ), while caregivers’ emotional problems were assessed by the Depression Anxiety Stress Scales-21. Structural equation modeling was employed to estimate the direct and indirect associations (explained by caregivers’ emotional problems) between COVID-19 related knowledge and precautions, and children’s EBPs. The overall prevalence of EBPs in the sample was 12.5%, and 5.3% had a high or very high SDQ total difficulties score during the COVID-19 post-pandemic. After adjustment for covariates, higher COVID-19 related knowledge (β=-0.83; P<0.001) and precautions (β=-0.80; P<0.001) were significantly associated with lower SDQ total difficulties score among children. There was an explanatory effect of caregivers’ emotional problems on the aforementioned associations, which explained 31% and 41% of the total effect respectively. Higher levels of knowledge and precautions of COVID-19 were associated with lower children’s EBPs, and the relationship was partially explained by caregivers’ emotional problems. It may be beneficial to improve pandemic-related prevention education and adopt psychological interventions towards caregivers’ emotional status for children’s psychological health.